The impact of tax treaties on foreign direct investment: The evidence reconsidered - Siwook Lee; Daeyong Kim (KDI Journal of Economic Policy, 2022)
This paper reconsiders the empirical evidence of the relationship between tax treaties and FDI using U.S. outbound FDI to 78 countries over the period of 2007-2018. Unlike previous studies, we explicitly consider differences in the tax environments of recipient economies, including their tax-haven status, transfer pricing rules, CFC rules and anti-avoidance regulations, in our estimations. Our results confirm the importance of controlling for country-specific tax environments, especially the tax-haven status and transfer pricing rules. We find that tax treaties positively contribute to FDI inflows in developing countries, while they have no statistically significant impacts on OECD countries. Recently signed tax treaties still foster FDI but less than older ones do. Finally, our results indicate, all other things being equal, that the weaker the transfer pricing regulations, the greater the amount of U.S. direct investment into a non-OECD economy.
Keywords: O11; O47; C21; F4; 330; Tax Treaties; Foreign Direct Investment; Tax Havens; Transfer Pricing; Tax Regulations